Exploring human resource management in the top five global hospitals: a comparative study - Wang, Xingyou; Wang, Richard Szewei; Qin, Xiaoping; Huang, Yu-Ni; Chiu, Herng-Chia; Wang, Bing-Long (Frontiers in Public Health, 2024)
Background: The pivotal role of Human Resource Management (HRM) in hospital administration has been acknowledged in research, yet the examination of HRM practices in the world's premier hospitals has been scant. Objective: This study explored how the world's leading hospitals attain operational efficiency by optimizing human resource allocation and melding development strategies into their HRM frameworks. A comparative analysis of the HRM frameworks in the top five global hospitals was undertaken to offer a reference model for other hospitals. Methods: This research offers a comparative exploration of the HRM frameworks utilized by the top five hospitals globally, underscoring both shared and distinct elements. Using a multi-case study methodology, the research scrutinized each hospital's HRM framework across six modules, drawing literature from publicly accessible sources, including websites, annual reports, and pertinent Englishlanguage scholarly literature from platforms such as Google Scholar, PubMed, Medline, and Web of Science.